A psychological study on school organizational climate in relation to teachers job satisfaction among primary school teachers in Northern Jiangsu, China - Jing, Xie; Abdul Aziz, Nor Azni (ReAttach Therapy International Foundation, 2023)
This study explores the relationship between school organizational climate and teachers job satisfaction among primary school teachers in northern Jiangsu, China. The theoretical underpinning of this study is Herzberg's Two-Factor Theory and Halpin, as well as Croft's School Organizational Climate Theory. This is a descriptive correlation study, conducted in northern Jiangsu, China, covering the districts of Huaian, Yangzhou, and Xuzhou. The instrument used for data collection was a survey in the form of a structured questionnaire. The responses of 234 participants were recorded, which contain information on gender, age, level of education, teacher experience, and school location. This data was then analysed quantitatively. The results indicated that a democratic and people-oriented climate in schools can improve teachers' job satisfaction. Adequate support for teachers, sufficient school resources, harmonious interpersonal relationships, and a moderate workload can boost and maintain teachers' job satisfaction at a high level. This would in turn improve teachers' teaching ability and effectively promote the development of schools psychologically. This study then proposes several recommendations to school administrations and teachers on how to improve the level of teachers job satisfaction through the creation and maintenance of a positive school organizational climate.